Development of 3D bioprinting: From printing methods to biomedical applications - Gu, Zeming; Fu, Jianzhong; Lin, Hui; He, Yong (Asian journal of pharmceutical sciences, 2020)
Biomanufacturing of tissues/organs in vitro is our big dream, driven by two needs: organ transplantation and accurate tissue models. Over the last decades, 3D bioprinting has been widely applied in the construction of many tissues/organs such as skins, vessels, hearts, etc., which can not only lay a foundation for the grand goal of organ replacement, but also be served as in vitro models committed to pharmacokinetics, drug screening and so on. As organs are so complicated, many bioprinting methods are exploited to figure out the challenges of different applications. So the question is how to choose the suitable bioprinting method? Herein, we systematically review the evolution, process and classification of 3D bioprinting with an emphasis on the fundamental printing principles and commercialized bioprinters. We summarize and classify extrusion-based, droplet-based, and photocuring-based bioprinting methods and give some advices for applications. Among them, coaxial and multi-material bioprinting are highlighted and basic principles of designing bioinks are also discussed.